2017
DOI: 10.1080/02791072.2017.1301600
|View full text |Cite
|
Sign up to set email alerts
|

Massachusetts Substance Use Disorder Treatment Organizations’ Perspectives on the Affordable Care Act: Changes in Payment, Services, and System Design

Abstract: The Affordable Care Act (ACA) expanded insurance benefits and coverage for substance use disorder (SUD) treatment and encouraged delivery and payment reforms. Massachusetts passed a similar reform in 2006. This study aims to assess Massachusetts SUD treatment organizations’ responses to the ACA. Organizational interviews addressing challenges of and responses to the ACA were conducted in-person June–December 2014 with 31 leaders at 12 treatment organizations across Massachusetts. Many organizations were affili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…32 Behavioral health providers have struggled with attempting to modernize their workforce and business practices and have received limited TA in some states to address these struggles since reforms resulting from the passage of the ACA 33 A study among Massachusetts SUD treatment organizations found that providers faced similar challenges as they were responding to ACA reforms in terms of expansion of services and clinical practices, workforce development, and IT infrastructure. 34 This highlights that significant support to providers is needed to improve the SUD treatment system as well as more research to understand barriers and facilitators to making system-level quality improvements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32 Behavioral health providers have struggled with attempting to modernize their workforce and business practices and have received limited TA in some states to address these struggles since reforms resulting from the passage of the ACA 33 A study among Massachusetts SUD treatment organizations found that providers faced similar challenges as they were responding to ACA reforms in terms of expansion of services and clinical practices, workforce development, and IT infrastructure. 34 This highlights that significant support to providers is needed to improve the SUD treatment system as well as more research to understand barriers and facilitators to making system-level quality improvements.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] Implementing quality improvement (QI) programs and expanding the use of technology will become essential to monitoring quality metrics and improving outcomes. 9,13,14 Developing partnerships with larger healthcare systems and other support services (eg, housing) may also be necessary to ensure all client needs are addressed. 9,14 VBP arrangements, as well as the clinical and business practices that are meant to improve quality, represent a significant shift for behavioral health providers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations